The Role of Monoclonal Antibody in Combination with First-Line Chemotherapy in Asian Patients with Advanced Non-Small Cell Lung Cancer - Cho, Byoung Chul; Kim, Joo Hang; Soo, Ross A; Yang, Chih-Hsin (Yonsei medical journal, 2010)
The strategies of incorporating monoclonal antibodies (MoABs) have now proved efficacy in the first-line treatment of advanced non-small cell lung cancer (NSCLC). These include targeting the vascular endothelial growth factor (VEGF) or epidermal growth factor receptor (EGFR). Bevacizumab is a MoAB targeting the vascular endothelial growth factor (VEGF), an important mediator of new blood vessel formation. Cetuximab is a MoAB directed at EGFR. Binding cetuximab to EGFR blocks signal transduction and promotes receptor internalization and degradation. In this review, we present current data of bevacizumab and cetuximab for the first line treatment of advanced NSCLC. We also refer to their potential for Asian patients with advanced NSCLC in the first-line setting.